ANALISIS HUKUM TERHADAP TINDAK PIDANA KORUPSI DALAM PROYEK JALAN TOL MBZ: Legal Analysis of Corruption in the MBZ Toll Road Project - Aulia, Mohamad Donie (Res Nullius Law Journal, 2025)
Acts of corruption in various sectors of people's lives hinder economic growth and undermine public trust in the government and democratic principles. This study analyzes the corruption business crime in the MBZ Expressway project by using legal principles as the framework of analysis. Corruption in this project has a negative impact on two important aspects: the efficiency of the use of public budget and transparency in project management. Research shows that the application of the principles of legality, transparency, fairness, proof, and prevention is essential to prevent corrupt practices. The principle of legality ensures that all legal actions follow clear regulations, while transparency provides access to the information necessary for accountability. Justice guarantees fair treatment of all parties in the procurement and law enforcement process. Building awareness of ethics and integrity among government officials and business people is essential, supported by training that emphasizes ethical decision-making and the establishment of effective oversight systems, including independent audits and public scrutiny. The consistent implementation of these legal principles is expected to reduce corrupt practices and increase public confidence in the management of infrastructure projects. Success in eradicating corruption requires strong law enforcement and cultural change that supports integrity and accountability.